2021
DOI: 10.1093/inthealth/ihab053
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of long-acting reversible contraceptive use among sexually active women in 26 sub-Saharan African countries

Abstract: Background Long-acting reversible contraceptives (LARCs) are associated with high efficacy rates and continuity of use. Based on the foregoing, we sought to examine the prevalence and factors associated with LARC use among sexually active women in 26 countries in sub-Saharan Africa(SSA). Methods Secondary data from Demographic and Health Surveys conducted in 26 countries in SSA between January 2010 and December 2019 were pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 43 publications
8
35
2
Order By: Relevance
“…Increased educational attainment especially secondary school and above influence service use of and female decision-making power on reproduction health issues particular family planning. The findings agrees with other studies conducted in Kenya, Ethiopia and Uganda that had shown that higher education is an important predictor of LAPM use [ 23 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased educational attainment especially secondary school and above influence service use of and female decision-making power on reproduction health issues particular family planning. The findings agrees with other studies conducted in Kenya, Ethiopia and Uganda that had shown that higher education is an important predictor of LAPM use [ 23 , 59 , 60 ].…”
Section: Discussionsupporting
confidence: 92%
“…Independent variables were identified based on a review of literature of previous studies on LAPM [ 19 , 30 , 31 , 37 44 ] and included age measured in completed years at the time of the interview categorized into age groups (15–19, 20–29, 30–39, and 40–49 years); level of education (none, primary, and secondary and above), household wealth tercile (poor, middle, and rich), future fertility preference (no more/none and have ((an)other) child(ren), number of children ever born (CEB) as at the time of the survey (0–2, 3–5 and 6 or more), exposure to media was classified as yes for those who had listened to radio or watched television or read newspaper or accessed social media at least once a week and no for those who had not [ 23 ] and the main decision-maker on a woman’s health (woman alone, woman with a partner, and other). The other decision-makers included the husband/partner alone, father or father-in-law, mother or mother-in-law, other male family members, and other female family members.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] Population-based studies have estimated that the use of LARCs among married women ranged from 1.9% to 55.0% in Africa. [ 15 , 25 ] A nationwide study reported that approximately 5% of currently married Nepalese women of reproductive age use LARCs. [ 16 ] The evidence shows that the use of LARCs reported in the current study is higher than that reported by the Nepalese study but within the range reported in SSA, which could be attributed to differences in the study population as well as access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search yielded studies that investigated the use of LARCs among reproductive women in sub-Saharan Africa (SSA) [ 14 , 15 ] and Nepal. [ 16 ] Nonetheless, the emphasis, study sample, or geographical location of these related studies limits their generalizability to the study setting.…”
Section: Introductionmentioning
confidence: 99%